The clinical efficacy of percutaneous endoscopic lumbar discectomy combined with platelet-rich plasma injection for lumbar disc herniation: a systematic review and meta-analysis - Hua Song; Ying Zhang (Frontiers in Surgery)
ObjectiveAlthough percutaneous endoscopic lumbar discectomy (PELD) has shown favorable outcomes in the treatment of LDH patients, the issue of recurrence caused by potential disc degeneration remains unresolved. Regenerative therapy with platelet-rich plasma (PRP) injection offers the potential to reduce recurrence rates and improve clinical outcomes. This systematic review and meta-analysis evaluated the clinical efficacy of combining PELD with PRP injection as a novel therapeutic approach for LDH.MethodsA comprehensive literature search was conducted in the PubMed, Embase, Web of Science, and Cochrane databases, with the search period ending on October 30, 2024. Data were extracted and analyzed to evaluate recurrence rates, pain relief, functional outcomes, and intervertebral disc health status.ResultsA total of 4 eligible studies were identified in this research, comprising 421 patients, of whom 212 received the combined treatment of PRP and PELD, while 209 underwent PELD alone. The results demonstrated that the combined PELD and PRP therapy significantly reduced recurrence rates (OR: 0.21, 95% CI: 0.07 to 0.64, p = 0.006) and improved VAS pain scores for both back and leg pain at specific follow-up time. Additionally, intervertebral disc height at the final follow-up was significantly greater in the combined PELD and PRP group (MD: 0.88, 95% CI: 0.57 to 1.20, p < 0.00001), indicating the potential of the combined therapy to restore degenerative discs.ConclusionsThe study indicates that PELD combined with PRP therapy provides better clinical outcomes compared to PELD alone, particularly in reducing recurrence rates, alleviating pain, and improving functional recovery. However, future studies with larger sample sizes and extended follow-up durations are warranted to validate the long-term efficacy and safety of this innovative therapeutic approach.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024621150, PROSPERO CRD42024621150.